Economie en apartheid : westerse investeringen in Zuid-Afrika - First, Ruth; Steele, Jonathan; Gurney, Christabel (Amsterdam : Van Gennep, 1974)
Bibliotheek François Vercammen
Nederlands
Monografie
Keywords: economie; apartheid; Zuid-Afrika.